AGN and Star Formation Feedback in Galaxy Outflows. Issue Volume 14:Issue S342(2019) (May 2018) - de Gouveia Dal Pino, Elisabete M.; Clavijo-Bohórquez, William; Melioli, Claudio
Abstract: Large-scale, broad outflows are common in active galaxies. In systems where star formation coexists with an AGN, it is unclear yet the role that both play on driving the outflows. In this work we present three-dimensional radiative-cooling MHD simulations of the formation of these outflows, considering the feedback from both the AGN and supernovae-driven winds. We find that a large-opening-angle AGN wind develops fountain structures that make the expanding gas to fallback. Furthermore, it exhausts the gas near the nuclear region, extinguishing star formation and accretion within a few 100.000 yr, which establishes the duty cycle of these outflows. The AGN wind accounts for the highest speed features in the outflow with velocities around 10.000 km s −1 (as observed in UFOs), but these are not as cold and dense as required by observations of molecular outflows. The SNe-driven wind is the main responsible for the observed mass-loading of the outflows.